Convergent Morphological Evolution in Silene Sect. Italicae (Caryophyllaceae) in the Mediterranean Basin - Naciri, Yamama; Toprak, Zeynep; Prentice, Honor C.; Hugot, Laetitia; Troia, Angelo; Burgarella, Concetta; Gradaille, Josep Lluis; Jeanmonod, Daniel (Frontiers in Plant Science, 2022)
Recent divergence can obscure species boundaries among closely related taxa. Silene section Italicae (Caryophyllaceae) has been taxonomically controversial, with about 30 species described. We investigate species delimitation within this section using 500 specimens sequenced for one nuclear and two plastid markers. Despite the use of a small number of genes, the large number of sequenced samples allowed confident delimitation of 50% of the species. The delimitation of other species (e.g. Silene nemoralis, S. nodulosa and S. andryalifolia) was more challenging. We confirmed that seven of the ten chasmophyte species in the section are not related to each other but are, instead, genetically closer to geographically nearby species belonging to Italicae yet growing in open habitats. Adaptation to chasmophytic habitats therefore appears to have occurred independently, as a result of convergent evolution within the group. Species from the Western Mediterranean Basin showed more conflicting species boundaries than species from the Eastern Mediterranean Basin, where there are fewer but better-delimited species. Significant positive correlations were found between an estimation of the effective population size of the taxa and their extent of occurrence (EOO) or area of occupancy (AOO), and negative but non-significant correlations between the former and the posterior probability (PP) of the corresponding clades. These correlations might suggest a lower impact of incomplete lineage sorting in species with low effective population sizes and small distributional ranges compared with that in species inhabiting large areas. Finally, we confirmed that S. italica and S. nemoralis are distinct species, that S. nemoralis might furthermore include two different species and that S. velutina from Corsica and S. hicesiae from the Lipari Islands are sister species.